Penguatan Pendidikan Karakter Sebagai Upaya Mencegah Terjadinya Bullying di SMA Negeri 1 Narmada - Sumasni; Muhammad Mabrur Haslan; Sawaludin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the forms of Bullying behavior in the school environment, examine the implementation of the Strengthening Character Education (PPK) program as a prevention strategy, and identify internal and external factors influencing the success of PPK at SMAN 1 Narmada, West Lombok, West Nusa Tenggara. The problem of Bullying in high schools is increasingly complex with the increasing influence of social media and uncontrolled peer group dynamics. This study is a response to the urgency of addressing Bullying holistically through a structured and sustainable character education approach. The method used is a qualitative case study approach, which allows researchers to gain an in-depth understanding of the Bullying phenomenon in a specific school context. Data were collected through semi-structured interviews with 12 purposively selected informants, participant observation of learning and habituation activities, and documentation in the form of school regulations, BK case files, and lesson plan documents. Data analysis used the Miles & Huberman interactive model, including data reduction. data presentation, and conclusion drawing. Data validity was verified through triangulation of sources and techniques. The research results show that the most dominant form of Bullying is verbal Bullying, which includes physical teasing, economic harassment, and negative nicknames, followed by social Bullying, which involves exclusion and the formation of exclusive groups, and mild physical Bullying, often seen as joking. The implementation of PPK (Community Empowerment and Child Protection) is carried out through the integration of character values into learning, the instilling of school culture through the 5S program and Saturday Culture, the exemplary behavior of teachers and principals, and active collaboration with parents. Supporting factors include discipline and the role of guidance and counseling teachers, while inhibiting factors include a non-conducive family environment, peer influence, and the negative impact of social media. This study concludes that the consistent, collaborative, and value-based implementation of PPK is effective in reducing Bullying behavior, although challenges from external factors still require ongoing attention from all educational stakeholders.